Numerical study of cold-formed steel frame walls under compression loading. Issue 14 (9th November 2022) - Samiee, Parisa; Esmaeili Niari, Shirin; Ghandi, Elham
Abstract: Bearing walls in cold-formed steel buildings act as a transmitter of vertical loads of the building and as a retainer of the exterior of the building and also absorb the lateral loads of the building such as wind and earthquake loads. In this article, the behaviour of cold-formed steel frame walls under compressive axial load has been investigated numerically. First, the finite element model of the cold-formed steel wall was developed using ABAQUS software, and then, structural analysis was performed, taking into account the effects of geometric and materials nonlinearities. The results of the numerical model were compared with the experimental results to confirm the accuracy of the numerical model. In the following, parametric studies have been carried out considering some parameters affecting the behavior and the ultimate load of cold-formed steel frame walls such as type of sheathing, stud web depth, stud flange width and stud cross-section shape. The results of the structural analysis showed that the type of wall sheathing did not have a significant effect on the ultimate load of the wall, but increasing the web depth of the stud, has led to a decrease in the load-bearing capacity of the steel wall. The wall with hollow flange studs has a higher ultimate load than other sections, and also, the use of web stiffened stud leads to an increase in the final bearing capacity of the wall compared to typical sections.